Heavy metals in river Vardar - Grizo, Aleksandar (Macedonian Journal of Ecology and Environment, 1995)
The average concentration of heavy metals: lead, cink, cadmium and chromium 6+, in the river Vardar in the periods 1981/85,1990 and 1993 are presented. The relative contribution of natural and anthropogenic concentrations of heavy metals in the river Vardar were derived.